Kajian Eksperimental pada Turbin Screw Archimedes Skala Kecil - Rahmawaty, Rahmawaty; Suherman, Suherman; Dharma, Surya; Sai'in, Ali (Jurnal Rekayasa Mesin, 2022)
The number of rivers and canals in most parts of Indonesia is large enough to be developed into a micro-hydro power plant. The Archimedes srcew turbine (Archimedes scew turbine AST) has been implemented to convert hydroelectric energy since the 1990s. Many variables affect the performance of Archimedes screw turbines such as pitch ratio, immersion rate, water flow and turbine shaft angle. The purpose of this study was to determine the effect of the turbine shaft inclination angle (25-35o) on the rotation, current and voltage produced by the screw turbine. The screw turbine has a diameter of 260 mm with a shaft length of 1200 mm and a pitch distance of 200 mm. The flow rate of water is used at 0,0065 m3/s to rotate a low speed generator. The results showed that the higher the turbine shaft angle resulted in an increase in rotation, voltage and current produced. The optimum angle is obtained at a turbine angle of 35o which produces 2,058 Watts at 243 rpm.